Peter Howitt: A Keynesian still in recovery - David E. W. Laidler (The University of Western Ontario, Department of Economics, 2022)
Peter Howitt is best known for his contributions to growth theory, but his work in short- run economics, which began with his Ph.D thesis and still continues, is important and deserves attention. It lies firmly in the Keynesian macro-disequilibrium tradition of Clower and Leijonhufvud, and for a long time has been overshadowed by New-classical and New-Keynesian orthodoxy. However, the development of agent based modelling and behavioural economics will perhaps give disequilibrium macroeconomics a new lease on life.
Keywords: B22; B59; E12; E13; E31; E32; 330; equilibrium; disequilibrium; money; New classical Economics; New KeynesianEconomics; Keynes; Lucas; Howitt; Clower; Leijonhufud; Phelps